ANALISIS PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT BATIK KERIS DI SURAKARTA - Tiara Kusumarla Ningrum; Zandra Dwanita Widodo; Laksono Sumarto (Universitas Bina Taruna Gorontalo, 2023)
This study has a goal, namely to be able to determine the effect partially or simultaneously on the variables of leadership, work discipline, motivation on employee performance. In order for management activities to work optimally, the organization must have competent and trained workers and then efforts to operate the organization as well as possible to improve employee performance. This shows that it is increasingly clear that the position of human resources in a company is an important asset that must be managed properly and correctly. This research was conducted on PT Batk Keris employees who are located at Jalan Perintis Kemerdekaan No. 1. Surakarta. The population is all employees as many as 50 people, then all are taken as samples (saturated sampling). The results of the study can be stated that there is a partial and simultaneous influence of the variables of leadership, work discipline and work motivation on employee performance. The influence of the three independent variables turns out to be the leadership variable that has the most dominant influence on the ups and downs of employee performance. The influence of the variables of leadership, work discipline and motivation is 88.60%, while the remaining 11.40% is influenced by other factors that are not included in this study.